Investigating leaf lifespans with interval-censored failure time analysis - Dungan, Roger J (The New phytologist, 2003)
•  Here leaf lifespans were investigated using interval-censored failure time analysis. The utility of this relatively novel approach is illustrated by comparing the leaf lifespan of winter-deciduous fuchsia (Fuchsia excorticata) and annual-evergreen wineberry (Aristotelia serrata). •  Leaf emergence and mortality were first described using growth equations. Individual leaf lifespans were investigated using a parametric failure-time regression model that accounted for the interval-censored nature of leaf lifespan data. •  Bud burst began 7 d earlier, the rate of leaf emergence was 0.06 leaves per shoot d-1 faster, and emergence ended 44 d earlier in fuchsia than in wineberry. The rate of leaf mortality was greatest in mid-summer in fuchsia, but nearly constant over the year for wineberry. There was a highly significant effect of the date of leaf emergence on leaf lifespan. Leaves emerging earlier in the growing season had shorter lifespans relative to later emerged leaves in fuchsia, whereas the reverse was true for wineberry. There was no significant effect of shoot height, branch order, or the number leaves of per shoot length on leaf lifespan. •  These results highlight the utility of studying phenology at the individual leaf level using failure time analysis. Although growth equations precisely describe leaf emergence and mortality in wineberry and fuchsia, they obscured key differences between the species that were identified using failure time analysis